Fikih Sosial: Ekspansi Moderasi Islam untuk Peradaban Dunia - Nikmah, Shofiatun (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Exporting Islamic moderation in Indonesia to the World is a big work that requires a mature strategy and readiness. Thus, the importing world can replicate Islamic moderation in Indonesia with the various formulations offered. Social fiqh can be bargained to formulate the strategy of exporting Islamic moderation. Social Fiqh ideas by Kiai Sahal Mahfudz have a strong concept and established epistemology and continue to prioritize moderation (wasathiyyah) which the study still adheres to authenticity (al-Ashlaah) and accommodates modernity (al-Hadathah). The proximity of Muslims in the Middle East to Islamic text is an opportunity for the development of social jurisprudence in an effort to export Islamic Moderation. This study aims to formulate a strategy for exporting religious moderation through the Social Fiqh Approach, the idea of ​​Kiai Sahal, with a grounded theory approach and is qualitative in the method. This study shows that there are four formulations to make Social Fiqh a bargaining power; first, Middle Eastern students are awarded scholarships to study social fiqh and its implementation in Indonesia at Parent Universities such as STAIMAFA and universities that focus on social fiqh studies. Second, methodological studies of social fiqh are enriched through translation into foreign languages, scientific studies, and international conferences as bargaining for Islamic moderation in Indonesia. Third, conducting multitrack diplomacy towards Middle Eastern countries that there is an Indonesian-style fiqh methodology whose implementation can be adapted to the socio-political conditions in the importing country. Fourth, the development of social jurisprudence into civilization fiqh through multidisciplinary studies, so that various phenomena can be analyzed.